The Relationship between Reinforcement of Employee’s Customer-Centric Behavior and Employee Motivation Factors. - Kang, Eungoo (Advances in Social Sciences Research Journal, 2020)
Currently, there is little doubt that factors such as intensifying competition, high job turnovers, increased market diversity and technological advances demand the present organizations to invest in strategies that encourage customer-centric behaviors. To overcome these challenges and ensure employees to be more customer-oriented, the present author suggests integrated solutions based on prior major motivation theories such as Theory X and Y, Maslow's theory and Herzberg's two factor theory. As a result, the present research explains methods that companies can use to ensure that employees are motivated and satisfied, insisting that employee satisfaction and motivation play a huge role in ensuring that the organization is running smoothly and effectively. Also, the present author points out that adopting better employee incentive programs motivate employees to embrace practices that ensure customer satisfaction and company productivity. Organizations that fail to use the most appropriate incentives to drive their employees suffer huge losses.